NVESTIGATION ON TUNA FISHERIES ASSOCIATED WITH FISH AGGREGATING DEVICES (FADs) IN INDONESIA FMA 572 AND 573 - Agustinus Anung Widodo; Wudianto wudianto; Lilis Sadiyah; Mahiswara Mahiswara; Craig Proctor; Scott Cooper (Indonesian Fisheries Research Journal, 2020)
The use of anchored fish aggregating devices (a-FADs) in the Indonesia-Indian Ocean has increased rapidly. Since 2004, the Government of Indonesia has issued various FAD related fisheries regulations; however, its implementation was difficult, largely due to the lack of such information. As an endeavor to improve the management of tuna fisheries associated with FADs in this area, an Indonesia–Australia research collaboration project conducted a port sampling program from November 2013 to December 2015 in three key fishing ports in the western Indonesia, i.e., Pelabuhanratu (West Jawa), Muara Padang (West Sumatera), and Bungus (West Sumatera). Data were collected through daily enumeration and interviews with skippers, which consisted of catch, trip duration, biological data, and number of FADs visited. These data were analyzed to estimate catch rate, success rate, and length frequency distribution. The success rate of hand line/trolling line (HL/TR) at Muara Padang showed much lower than that at Pelabuhanratu. This may be due to more a-FADs or higher density in the Padang region, competing with purse seine (PS) boats operating in the same area, than those in the Pelabuhanratu region. The species composition caught by HL/TR and PS associated a-FADs in Indonesian FMA 572 and 573 include skipjack (SKJ, Katsuwonus pelamis), yellowfin (YFT, Thunnus albacares) and bigeye tuna (BET, T. obesus). A large proportion of the SKJ, YFT and BET caught at both Indonesian FMA 572 and 573 were juvenile fish, below the reported length at maturity (Lm) for those species.